CHILDREN'S AGE AND PARENTING STYLE IN CHILDREN WITH SPEECH DELAY - Suharto, Idola Perdana Sulistyoning; Yunalia, Endang Mei; Jayani, Indah; Karingga, Devangga Darma; Lindia, Hessy (International Journal of Patient Safety and Quality, 2024)
Background: Speech delay is a state of speech development that has below average quality. Speech delay is influenced by several factors including the children’s age and parenting style. The aim of this study was to determine the relationship between child age and parenting patterns with speech delay. Method: The study was cross-sectional, with a sample size of 70 respondents which from pediatric patients at Kediri Physiotherapy Clinic in 2023, obtained through accidental sampling. The study’s dependent variable was speech delay, and the independent variables were the children's age and parenting style. The instrument used is a questionnaire. Data were collected using a questionnaire analyzed by chi square statistical test. Result: Most children were male (51 respondents) on pre-school with 1 of siblings (42 respondents). Parents were mostly on high level education and they use authoritarian parenting style for their children. Chi square statistical test show that there is no relationship between the children's age and speech delay (p-value = 0,271), and there is a relationship between parenting style and speech delay (p-value = 0.000). Conclusion: Parenting style has a correlation with speech delay. Therefore, the role of parents in providing parenting was very important for children's development. Parents must pay attention to provided stimulation and interaction with children, it was very important for children's growth and development, because the role of parents in caring for children was very impactfull.